Transboundary Movements of Waste - Bernard, Sophie (Université d'Ottawa | University of Ottawa, 2010)
In a stylized model of international trade, a monopolist in the North exports second-hand products to a representative firm in the South to be reused as intermediate goods, with potential trade gains. The degree of reusability of waste products is a crucial choice variable in the North. This is because with a lack of international vigilance, non-reusable waste can be mixed illegally with the reusable waste. I explore the driving forces for the movement of illegal waste, paying particular attention to the role of local waste regulations, such as the EU's Waste Electrical and Electronic Equipment directive. Under mild conditions, it is shown that increased regulation stringency in the North leads its firm to reduce the degree of reusability of its products. As a result, the flow of non-reusable waste to the South increases, providing another channel for the Pollution Haven Hypothesis. / Dans un modèle stylisé de commerce international, un monopole du Nord exporte, avec un potentiel de gain à l'échange, des biens de seconde-main qui seront réutilisés comme biens intermédiaires par une firme représentative du Sud. Le degré de réutilisabilité des produits en fin de vie est une variable de choix importante dans le Nord puisqu'en raison d'un manque de vigilance internationale, l'expédition illégale de biens non-réutilisables s'immisce avec l'exportation légitime de biens. Le modèle explore les causes du mouvement illégal des déchets en portant une attention particulière à la réglementation sur la gestion des déchets telle que la directive européenne sur les déchets d'équipements électriques et électroniques. Sous certaines conditions faibles, les résultats indiquent qu'une réglementation plus stricte dans le pays du Nord incite le monopole à réduire la réutilisabilité de ses produits. Traduit par un plus grand flux de déchets vers les pays en développement, ce résultat procure une voie alternative à l'hypothèse du paradis des pollueurs.
Keywords: second-hand products; illegal waste; environmental regulation; trade; biens de seconde-main; de?chet ille?gal; re?glementation environnementale; commerce